Clinical variability and female penetrance in X-linked familial FTD/ALS caused by a P506S mutation in UBQLN2. Issue 7 (December 2013) - Vengoechea, Jaime; David, Marjorie P.; Yaghi, Shadi R.; Carpenter, Lori; Rudnicki, Stacy A.
Abstract: Amyotrophic lateral sclerosis (ALS) is a degenerative motor neuron disease leading to progressive paralysis that is generally fatal. Only 10% of cases are familial, a subset of which overlaps with frontotemporal dementia (FTD). Up to half of ALS patients have cognitive impairment, with 15% meeting the criteria for FTD. Clinical sequencing of UBQLN2 in a family with X-linked FTD/ALS with suspected incomplete penetrance, manifesting in both genders, revealed a P506S mutation in. Affected individuals were diagnosed with various conditions including hereditary spastic paraplegia (HSP), bulbar palsy and multiple sclerosis. The mutation in UBQLN2 was first identified in a 35-year-old female who presented with one year of progressive dysarthria, dyspnea, dysphagia, and cognitive decline. EMG suggested early motor neuron disease with prominent bulbar involvement. Her cognition declined rapidly and she developed extremity weakness. Her brother, initially diagnosed with HSP, and her second cousin, with primary lateral sclerosis, also have a P506S mutation in UBQLN2 . In conclusion, the P506S mutation in UBQLN2 can affect both males and females and displays great phenotypic variability within the same family. Females can potentially have a more severe and rapidly progressive presentation than their male relatives. Additionally, the P506S mutation can also cause an FTD phenotype.